1998
DOI: 10.1159/000017326
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lactate and Glucose Metabolism in Cultured Neocortical Neurons and Astrocytes Using <sup>13</sup>C-NMR Spectroscopy

Abstract: In cerebral cortical neurons, synthesis of the tricarboxylic acid (TCA) cycle-derived amino acids, glutamate and aspartate as well as the neurotransmitter of these neurons, γ-aminobutyrate (GABA), was studied incubating the cells in media containing 0.5 mM [U-13C]glucose in the absence or presence of glutamine (0.5 mM). Lyophilized cell extracts were analyzed by 13C nuclear magnetic resonance (NMR) spectroscopy and HPLC. The present findings were compared to results previously obtained us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 45 publications
9
109
1
Order By: Relevance
“…However, direct comparison of relative rates of glucose and lactate oxidation are difficult to interpret because of the metabolic consequences of administering 'loading' (versus tracer) doses of labeled lactate and the many metabolic steps and metabolite pools between the labeled precursor and metabolites that must be analyzed to draw firm conclusions. Waagepetersen et al (1998) concluded that lactate is less efficient The expected precursor-product relationship (larger isotope enrichment in the precursor than in the product) is observed, since labeling of C4 in glutamine is secondary to [4-13 C]glutamate uptake by astrocytes and glutamine formation in these cells (from Gruetter et al, 2001). (B) [2-13 C]Acetate leads to an increase in glutamine labeling in C4 (filled circles), primarily due to net synthesis of glutamine in astrocytes, which with a normal precursor-product relationship is followed by slower labeling of C4 in glutamate (open squares), secondary to glutamine uptake by neurons and its conversion to glutamate (From Lebon et al, 2002).…”
Section: Determination Of Oxidative Activity In Astrocytes Via Three mentioning
confidence: 98%
“…However, direct comparison of relative rates of glucose and lactate oxidation are difficult to interpret because of the metabolic consequences of administering 'loading' (versus tracer) doses of labeled lactate and the many metabolic steps and metabolite pools between the labeled precursor and metabolites that must be analyzed to draw firm conclusions. Waagepetersen et al (1998) concluded that lactate is less efficient The expected precursor-product relationship (larger isotope enrichment in the precursor than in the product) is observed, since labeling of C4 in glutamine is secondary to [4-13 C]glutamate uptake by astrocytes and glutamine formation in these cells (from Gruetter et al, 2001). (B) [2-13 C]Acetate leads to an increase in glutamine labeling in C4 (filled circles), primarily due to net synthesis of glutamine in astrocytes, which with a normal precursor-product relationship is followed by slower labeling of C4 in glutamate (open squares), secondary to glutamine uptake by neurons and its conversion to glutamate (From Lebon et al, 2002).…”
Section: Determination Of Oxidative Activity In Astrocytes Via Three mentioning
confidence: 98%
“…Instead, they may convert some pyruvate to lactate and release the latter to the extracellular fluid, from which neurons extract it and oxidize it as a fuel. Neurons can respire on lactate (102), but they may require glucose as a substrate if they are to maintain large internal pools of glutamate and aspartate (125). Astrocytic release of lactate and subsequent neuronal oxidation may constitute a mechanism by which neuronal and metabolic activity are effectively coupled (33,66).…”
Section: Brain Metabolism Of Glucosementioning
confidence: 99%
“…In favour of a role of aspartate synthesis in astrocytes, 3 h incubation of astrocytes with pathological concentrations of ammonia and inhibition of GS with MSO increased de novo aspartate synthesis by 115-130 and 158-165% of control, respectively, and even to 200-290% after concomitant administration. 48 In favour of a proposed role of aspartate similar to that of alanine with regards to the alanine-lactate shuttle between neurons and astrocytes, exogenous glutamine stimulates aspartate synthesis from [U- 13 C 6 ]glucose in cortical neurons, 156 and aspartate nitrogen is transferred to alanine in astrocytes. 173 Furthermore, the uptake of aspartate from the incubation medium of cultured astrocytes is as rapid as that of glutamate, 215 and both compounds are utilized more rapidly than all other amino acids.…”
Section: Intercellular Cycling Of Ammonia Through Aspartate Synthesismentioning
confidence: 99%
“…21,90 Nonetheless, neuronal lactate utilization dominated. 92,116,117,156 Also glutamate is taken up very efficiently by astrocytes 163,164 at a rate of approx. 0.5 mmol/h/mg, which almost corresponds to the average value of glucose uptake ( Table 3).…”
mentioning
confidence: 99%